Yesus Sang Naga: Kontekstualisasi Kristologi Dalam Penghayatan Orang Tionghoa Di Indonesia - Sutanto, Florencia Paramitha Hapsari Hendra; Wahju Satria Wibowo (STFT Jakarta, Indonesia, 2024)
There was a time when Chinese Christians in Indonesia were prohibited from using symbols such as dragons, tigers, and snakes, which some Christian groups considered representations of evil. Items depicting dragons were recommended to be discarded after being prayed over, as the dragon is often used as a symbol of evil in the Bible. However, in Chinese culture, the dragon is seen as a positive and sacred symbol representing strength, luck, and wisdom. Birth rates increase during the Year of the Dragon, as it is believed to bring good fortune and success. This research examines the correlation between the understanding of Jesus in Christian belief and the dragon in Chinese culture, aiming to resolve the confusion faced by Chinese Christians in Indonesia regarding their dual identity. The dragon mentioned in the Bible is difficult to comprehend from the perspective of Chinese culture because the concepts differ. For Chinese Christians, exploring the symbolic meaning of the dragon in the Bible should be accompanied by a deeper understanding of their own cultural anthropology. It is important to note that the dragon in the Bible actually stems from Western cultural concepts, and understanding this difference is crucial for spiritual clarity. Failure to address this misconception can lead to the neglect or abandonment of Chinese cultural heritage, while considering European culture as superior. Therefore, it is essential to appreciate these conceptual differences as unique cultural riches without rejecting or replacing them, allowing each culture to value its own symbols while maintaining a rich and diverse cultural identity.